Intensi Melakukan Tindakan Plagiasi oleh Mahasiswa Akuntansi: Dampak Perkembangan Teknologi dan Unfair Competition - Briyan Efflin Syahputra; Anggit Esti Irawati; Nur Ariefin Addinpujoartanto (Jurnal Akademi Akuntansi, 2023)
Purpose: This study examines how technological development and unfair competition affect students' motivations to plagiarize. Methodology/approach: This study employs a quantitative methodology and a survey as its primary research tool. In order to gather information for this study, questionnaires were also used. 257 accounting students, including those pursuing diploma, bachelor's, master's, and doctoral degrees, who were enrolled in 16 universities in the Province of DIY made up the entire sample size for this study. Findings: Technological development and unfair competition have both been shown to have a positive impact on students' intentions to plagiarize. Practical and Theoretical contribution/Originality: The findings of this study can be used as a reference option for policy makers in various types of educational institutions, especially in tertiary institutions in order to develop effective anti-plagiarism policies. Research Limitation: This study was not carried out comprehensively to all universities in the Province of DIY that have Accounting Study Programs. The 257 respondents in this study only came from 16 universities. Considering that there are quite a number of universities in DIY that have Accounting Study Programs, it is hoped that future researchers will be able to broaden the range of respondents' origins.